Keep Them Engaged! Investigating the Effects of Self-centered Social Media Communication Style on User Engagement in 12 European Countries. (4th July 2022) - Bene, Márton; Ceron, Andrea; Fenoll, Vicente; Haßler, Jörg; Kruschinski, Simon; Larsson, Anders Olof; Magin, Melanie; Schlosser, Katharina; Wurst, Anna-Katharina
ABSTRACT: On Facebook, patterns of user engagement largely shape what types of political content citizens can see on the platform. Higher engagement leads to higher visibility. Therefore, one of the major goals of political actors' Facebook communication is to produce content with the potential to provoke user engagement, and thereby increase their own visibility. This study introduces the concept of self-centered social media communication style which focuses on "salient" and "owned" issues with populist and negative appeals and investigates how user engagement is related to its main elements. We also explore how users' receptivity to these content-related factors is shaped by country context. More specifically, we hypothesize that users are more likely to react, comment on and share posts focusing on salient topics or issues "owned" by parties rather than more permanent policy issues, and posts including populist appeals and negativity. Further, we test how these effects are moderated by geographical regions and the level of party system polarization. We manually coded 9, 703 Facebook posts of 68 parties from 12 European countries in the context of the 2019 European elections. Our findings show that users are more likely to engage with immigration-related, domestic, populist and negative posts, but react less to posts dealing with environmental or economic issues. While issue ownership does not play a significant role for user engagement, country context plays a minor role. However, some populist appeals are more effective in more polarized countries.